Giải hệ phương trình: \(\hept{\begin{cases}\left(x-1\right)y^2+x+y=3\\\left(y-2\right)x^2+y=x+1\end{cases}}\)
K
Khách
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
TU
1
![](https://rs.olm.vn/images/avt/0.png?1311)
25 tháng 11 2018
Đặt \(A=\sqrt{3+\sqrt{5-2\sqrt{3}}}-\sqrt{3-\sqrt{5-2\sqrt{3}}}\)
\(A^2=3+\sqrt{5-2\sqrt{3}}+3-\sqrt{5-2\sqrt{3}}-2\sqrt{9-5+2\sqrt{3}}\)
\(A^2=6-2\sqrt{4+2\sqrt{3}}=6-2\sqrt{3+2\sqrt{3}+1}=6-2\sqrt{\left(\sqrt{3}+1\right)^2}\)
\(A^2=6-2\left|\sqrt{3}+1\right|=6-2\left(\sqrt{3}+1\right)=6-2\sqrt{3}-2=4-2\sqrt{3}\)
Mà \(\sqrt{3+\sqrt{5-2\sqrt{3}}}>\sqrt{3-\sqrt{5-2\sqrt{3}}}\) nên \(\sqrt{3+\sqrt{5-2\sqrt{3}}}-\sqrt{3-\sqrt{5-2\sqrt{3}}}>0\)
\(\Rightarrow\)\(A=\sqrt{A^2}=\sqrt{4-2\sqrt{3}+1}=\sqrt{3-2\sqrt{3}+1}=\sqrt{\left(\sqrt{3}-1\right)^2}=\sqrt{3}-1\)
...
NH
3
![](https://rs.olm.vn/images/avt/0.png?1311)
25 tháng 11 2018
\(\sqrt[3]{x+1}=3\)
\(\Rightarrow x+1=3^3=27\)
\(\Rightarrow x=27-1=26\)
https://hoidap247.com/cau-hoi/792646